Determinants of agricultural cooperative performance using financial ratio - Zelhuda, Shamsuddin; Abdul Ghafar, Ismail; Suraya, Mahmood; Md Faruk, Abdullah (2017)
The main aim of this study is to examine the financial performance of agricultural cooperatives in Malaysia during the period of 2010-2014 using financial ratio (i.e. liquidity, leverage and asset efficiency). Based on the panel data model approach, the results of the study showed that liquidity, asset efficiency, dividend and cooperative size have significant relationship to performance. The outcome of this study would provide some insights to regulators, cooperative managements, and cooperative members towards designing and implementing future strategies to enhance cooperative performance.